ПРАКТИКА ЕВРОПЕЙСКОГО СУДА ПО ПРАВАМ ЧЕЛОВЕКА В ОБЛАСТИ ТРАНСПЛАНТАЦИИ ОРГАНОВ И ТКАНЕЙ ЧЕЛОВЕКА - Игорь, Арсени (SUPREMANCE OF LAW, 2018)
In this article, the author analyzes the main decisions of the European Court of Human Rights made in cases of transplantation and human organs and tissues, as well as cases to be considered. Based on the analysis carried out, the author identified the main mistakes made by the national courts when considering this category of cases and offered basic recommendations in order to eliminate existing problems and gaps in this area.